MEMBANGUN KEPERCAYAAN MASYARAKAT PADA MADRASAH MELALUI PAMEREN PENDIDIKAN - Yaqien, Nurul (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
Madrasah exhibition is an attempt of Islamic educational institution to acquaint itself to public till people know of its existence, advantages and superiority than the other schools. The exhibition is expected to demonstrate excellences of madrasah that will change public views so far, which are assumed madrasah is identical as backward, dirty and not advanced. Madrasah excellences are displayed on the society will make people excited and interested in Islamic educational institutions. The image and degrees of madrasah will be lifted as one of the advanced Islamic education institutions.Key word: Trust, Public, Exhibition, Madrasah